Identifikasi Daerah dengan Infrastruktur Telekomunikasi Tertinggal di Indonesia Menggunakan Algoritma UPGMA dan WPGMA - Raihannabil, Syfriza Davies; Wicaksono, Achmad Maulana Andi (Politeknik Statistika STIS, 2025)
Telecommunication infrastructure plays a crucial role in regional development in the digital era. Although ICT usage and mastery in Indonesia have improved, challenges remain in the equitable distribution of access and infrastructure. Using secondary data from the National Socio-Economic Survey (Susenas) by BPS, this study aims to identify regions with underdeveloped telecommunications infrastructure and determine the best hierarchical clustering algorithm. UPGMA and WPGMA were applied. The results show that UPGMA outperforms WPGMA, producing four optimal clusters: 1 province is very advanced, 4 are advanced, 28 are underdeveloped, and 1 is very underdeveloped. Therefore, the results of this study are expected to be the basis for formulating more targeted telecommunications infrastructure development policies, especially for areas that are classified as very underdeveloped, so that the digital divide can be reduced and inclusive digital transformation can be realized.